Digitizing Tiered Nursing Supervision in the Icu: Prototype Development and Usability Testing A Case Study - Rahayu Widiastuti; Hanny Handiyani; Kuntarti Kuntarti; Amelia Amelia (Indonesian Journal of Global Health Research, 2026)
Tiered nursing supervision in the Intensive Care Unit (ICU) has been routinely conducted; however, its impact on competency development and performance monitoring remains suboptimal due to the absence of a structured schedule, incomplete instruments and documentation, limited reflective practice and self-assessment, high workload, and supervisors’ time constraints. This case study aimed to initiate the development of a digital, tiered supervision prototype integrated with the hospital Electronic Medical Record (EMR). The change process was guided by Kotter’s eight-step model and aligned with nursing management functions (POSAC). Root causes were identified using an Ishikawa (fishbone) analysis based on the 5M framework. The study population consisted of ICU nursing personnel, with key informants (the ICU head nurse and nursing manager) selected through purposive sampling, and 36 ICU nurses meeting the inclusion criteria (≥2 years of experience and minimum PK-1 level) participating as survey respondents. Data were collected from May to June 2025 through semi-structured interviews, direct observations, and structured questionnaires distributed via Google Forms, with informed consent obtained from all participants. Data were analyzed descriptively and analytically using an Ishikawa (fishbone) diagram based on the 5M framework to identify root causes, followed by problem prioritization to inform the development and evaluation of a digital, tiered nursing supervision prototype. The innovation produced a supervision prototype comprising scheduling, standardized checklists, and evaluation outputs to support structured monitoring and feedback. A preliminary usability assessment using the System Usability Scale (SUS) yielded a score of 72/100, indicating acceptable usability. Further work is recommended to finalize integration with the existing EMR, conduct broader-scale testing, provide supervisor training, and strengthen a reflective and structured evaluation culture to comprehensively assess the system’s effectiveness.